2022
DOI: 10.1002/jctb.7019
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of valuable metals from the hydrochloric leaching solution of reduction smelted metallic alloys from spent lithium‐ion batteries

Abstract: BACKGOUND The recycling of valuable metals from spent lithium‐ion batteries (LIBs) has attracted much attention. This work investigated the recovery of cobalt (Co), nickel (Ni), copper (Cu), iron (Fe) and manganese (Mn) from metallic alloys generated from the reduction smelting of spent LIBs by a hydrometallurgical process. RESULTS The complete leaching conditions for metals from the alloys were optimized as: 2.0 mol L–1 hydrochloric acid (HCl), 5% (v/v) hydrogen peroxide (H2O2) with 30 g L–1 pulp density at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Although the stripping of Fe(III) from the loaded D2EHPA can be improved by using reducing agents such as SO2, H2SO3 and Na2SO3, multi-stage stripping is required for the complete stripping of Fe(III) [27]. In our previous studies, the complete stripping of Fe(III) from the loaded D2EHPA was obtained using aqua regia solution and the effect of aqua regia on the chemical structure of D2EHPA after the stripping was found to be insignificant [18]. Hence, in this work, aqua regia solution was employed for the stripping of Fe(III) from the loaded phase.…”
Section: Stripping Of Fe(iii) From the Loaded D2ehpamentioning
confidence: 99%
See 3 more Smart Citations
“…Although the stripping of Fe(III) from the loaded D2EHPA can be improved by using reducing agents such as SO2, H2SO3 and Na2SO3, multi-stage stripping is required for the complete stripping of Fe(III) [27]. In our previous studies, the complete stripping of Fe(III) from the loaded D2EHPA was obtained using aqua regia solution and the effect of aqua regia on the chemical structure of D2EHPA after the stripping was found to be insignificant [18]. Hence, in this work, aqua regia solution was employed for the stripping of Fe(III) from the loaded phase.…”
Section: Stripping Of Fe(iii) From the Loaded D2ehpamentioning
confidence: 99%
“…(aq) (7) Our previous studies showed that the complete leaching of metals from the alloys by acidic solutions required 2.0 mol/L HCl or H2SO4, 10% (v/v) H2O2 at 60 o C with 150 or 240 min reaction time [17,18]. Compared with the leaching of metals by acid solutions containing H2O2 as an oxidizing agent, either single Fe2(SO4)3 or FeCl3 solution showed some advantages in the recovery of metals such as: (1) the role of ferric salts as an oxidizing agent which would improve the process economics, (2) fast reaction kinetics, (3) low energy consumption due to leaching reactions at room temperatures, and (4) a decrease in the consumption of acids.…”
Section: Leaching Of Metals From the Alloys Using Single Fecl3 Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work, the combined processes for the recovery of valuable metals from sulfate and chloride solution from spent LIBs were reported 4,5) . Smelting reduction of spent LIBs at high-temperature results in metallic alloys containing Co, Ni, Cu, Fe, and Mn.…”
Section: Introductionmentioning
confidence: 99%